A new species of lowland karst-dwelling Slender Gecko Hemiphyllodactylus Bleeker, 1860 (Squamata: Gekkonidae) from a karstic archipelago in western Cambodia - L. Lee Grismer; Pablo Sinovas; Quah, Evan Seng Huat; Sothearen Thi; Phyroum Chourn; Sophea Chhin; Seiha Hun; Anthony Cobos; Peter Geissler; Christian Ching; Matthew L. Murdoch (Magnolia Press, 2025)
A new species of gekkonid lizard is described from Phnom Khpoh, an isolated karstic hill within an extensive karstic archipelago in Battambang Province, western Cambodia. Phylogenetic analysis using a 1041 base pair fragment of the mitochondrial gene ND2 recovered Hemiphyllodactylus khpoh sp. nov. as the sister species of H. pardalis, found 335 km to the west in southern Thailand. Analyses of meristic, morphometric, and categorical characters of morphology and color pattern differentiated H. khpoh sp. nov. from both the morphologically distinct H. pardalis and the very similar Hemiphyllodactylus sp. from Phnom Kulen, approximately 130 km to the northeast in Siem Reap Province. The statistical morphological analyses and comparisons also showed that H. khpoh sp. nov. is well-differentiated from the recently described H. bokor and H. samkos from the nearby Cardamom Mountains as well from species in clade 6—a recently designated lineage from China, Laos, and Vietnam to which H. khpoh sp. nov. + H. pardalis compose the sister lineage. The discovery of H. khpoh sp. nov. highlights the rich but understudied biodiversity of karstic landscapes, emphasizing the need for continued research in the extensive unexplored karstic archipelago of western Cambodia. This region is poised to reveal unparalleled gekkonid diversity, comparable to that observed in the similarly sized karstic archipelago of the Salween Basin in southern Myanmar. Although karstic landscapes are proving to be some of the most biodiverse habitats on the planet, less than 1% of them are afforded any formal protection.